Genomics-Based Phylogenetic and Population Genetic Analysis of Global Samples Confirms Halophila johnsonii Eiseman as Halophila ovalis (R.Br.) Hook.f. - Waycott, Michelle; van Dijk, Kor-jent; Calladine, Ainsley; Bricker, Eric; Biffin, Ed (Frontiers in Marine Science, 2021)
Halophila johnsonii is an endangered seagrass species that is restricted to the southeast coast of Florida, United States. Its taxonomic status has been called into question, in particular, given the close morphological and genetic similarity of H. johnsonii and the widely distributed and morphologically variable Halophila ovalis, which is largely restricted to the Indo-Pacific region. While a close relationship to H. ovalis is uncontroversial, it remains uncertain whether H. johnsonii represents a distinct lineage or is a recent introduction to the Florida region. Given the conservation status of H. johnsonii, distinguishing these alternatives has important implications for the management of the species and its habitat. Here, we develop molecular data sets for samples of H. johnsonii and H. ovalis including DNA sequences, genome-wide SNPs and microsatellites with the view to resolving the affinities of H. johnsonii with respect to the wider H. ovalis complex. Phylogenetic hypotheses based upon plastid (∼18000 bp) and low copy nuclear DNA (∼6500 bp) sequences derived from hybrid capture, along with 990 genome-wide ddRAD SNPs consistently resolved H. johnsonii within H. ovalis. Specifically, we found a close affinity between H. johnsonii and H. ovalis sampled from the east coast of Africa. In addition, Halophila specimens collected in Antigua, which are within the range of morphological variation typical for H. ovalis, are virtually identical to H. johnsonii and the East African H. ovalis samples based upon DNA sequence analyses and these group together using Bayesian clustering analyses of microsatellites and ddRAD SNPs. We conducted population genetic analyses using large number of H. johnsonii samples collected over a 17-year period. Genotypic data generated through microsatellites and ddRAD SNPs revealed genetic uniformity for all 132 H. johnsonii samples across the Indian River Lagoon, Florida, while samples of H. ovalis from Antigua shared the same genotype as H. johnsonii. We conclude that the lack of genetic diversity and the absence of sexual reproduction strongly indicates that the total range of H. johnsonii is actually one clone that is closely related to populations in Africa and Antigua and may be derived from a recent introduction from one of those regions.